Deficiency of LMP10 Attenuates Diet-Induced Atherosclerosis by Inhibiting Macrophage Polarization and Inflammation in Apolipoprotein E Deficient Mice - Liao, Jiawei; An, Xiangbo; Yang, Xiaolei; Lin, Qiu-Yue; Liu, Shuang; Xie, Yunpeng; Bai, Jie; Xia, Yun-Long; Li, Hui-Hua (Frontiers in Cell and Developmental Biology, 2020)
Macrophage polarization and inflammation are key factors for the onset and progression of atherosclerosis. The immunoproteasome complex consists of three inducible catalytic subunits (LMP2, LMP10, and LMP7) that play a critical role in the regulation of these risk factors. We recently demonstrated that the LMP7 subunit promotes diet-induced atherosclerosis via inhibition of MERTK-mediated efferocytosis. Here, we explored the role of another subunit of LMP10 in the disease process, using ApoE knockout (ko) mice fed on an atherogenic diet (ATD) containing 0.5% cholesterol and 20% fat for 8 weeks as an in vivo atherosclerosis model. We observed that ATD significantly upregulated LMP10 expression in aortic lesions, which were primarily co-localized with plaque macrophages. Conversely, deletion of LMP10 markedly attenuated atherosclerotic lesion area, CD68+ macrophage accumulation, and necrotic core expansion in the plaques, but did not change plasma metabolic parameters, lesional SM22α+ smooth muscle cells, or collagen content. Myeloid-specific deletion of LMP10 by bone marrow transplantation resulted in similar phenotypes. Furthermore, deletion of LMP10 remarkably reduced aortic macrophage infiltration and increased M2/M1 ratio, accompanied by decreased expression of pro-inflammatory M1 cytokines (MCP-1, IL-1, and IL-6) and increased expression of anti-inflammatory M2 cytokines (IL-4 and IL-10). In addition, we confirmed in cultured macrophages that LMP10 deletion blunted macrophage polarization and inflammation during ox-LDL-induced foam cell formation in vitro, which was associated with decreased IκBα degradation and NF-κB activation. Our results show that the immunoproteasome subunit LMP10 promoted diet-induced atherosclerosis in ApoE ko mice possibly through regulation of NF-κB-mediated macrophage polarization and inflammation. Targeting LMP10 may represent a new therapeutic approach for atherosclerosis.